Analyses of robust stablity of imc control systems - Phan, Vu Ngoc (Journal of Computer Science and Cybernetics, 2016)
The IMC structure of control systems shows advantages over the other control structures. The IMC structure permits US overcoming dificulties when a limitation of actuating magnitude as well as nonlinearity of the plant must be taken in account. The target of this paper is to describe the IMC control systems and their stability robustness. In Section 2 the normal feedback structure and the IMC structure is explained in order to make a comparison. Ill Section 3 the internal stability is generally defined and then the robust stability of some special IMC structures is studied.